A global-to-local sub modelling approach to investigate the effect of lubrication during double diaphragm forming of multi-ply biaxial non-crimp fabric preforms. (1st April 2023) - Yu, F.; Chen, S.; Lawrence, G.D.; Warrior, N.A.; Harper, L.T.
Abstract: The forming behaviour of preforms constructed from multiple plies of Non-Crimp Fabric (NCF) has been investigated for manufacturing a complex double-curved geometry using Double Diaphragm Forming (DDF). An established multi-resolution finite element forming simulation has been employed to investigate the effect of the ply layup sequence on the formation of fabric wrinkles. FE simulations are shown to be in good agreement with experiments performed using the same geometry, in terms of the location and number of fabric wrinkles, for layups containing single or multi-ply orientations. Simulation results indicate that the convex double-curved features on the tool surface induce fabric over-shearing, coupled with fabric bridging, leading to wrinkles. In addition, the dissimilar inter-ply shear deformations in multi-ply preforms result in local fibre compression causing additional wrinkles. Experiments confirm the feasibility of using liquid resin as an inter-ply lubricant to mitigate out-of-plane wrinkles, but this is found to compromise the stability of the fibre architecture in local convex regions, causing additional in-plane fibre misalignment.